2017
DOI: 10.7717/peerj.3511
|View full text |Cite
|
Sign up to set email alerts
|

The identification of Oligo-Miocene mammalian palaeocommunities from the Riversleigh World Heritage Area, Australia and an appraisal of palaeoecological techniques

Abstract: Fourteen of the best sampled Oligo-Miocene local faunas from the Riversleigh World Heritage Area, north-western Queensland, Australia are analysed using classification and ordination techniques to identify potential mammalian palaeocommunities and palaeocommunity types. Abundance data for these faunas are used, for the first time, in conjunction with presence/absence data. An early Miocene Faunal Zone B and two middle Miocene Faunal Zone C palaeocommunities are recognised, as well as one palaeocommunity type. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This is not sur- Results of the phylogenetic analysis with additional species added (relative branching order of these additional taxa are shown here as not resolved) against the geological time scale (Gradstein et al, 2012). Age span of deposits containing all known wombat taxa are provided, with black bars indicating certainty (such as radiometrically dated sites) and grey indicating uncertainty (ages are based on Archer and Wade, 1976;Archer et al, 1989Archer et al, , 1997Archer et al, , 2016Arena et al, 2016;Beck, 2008;Beheregaray et al, 2000;Black et al, 2012b;Cupper and Duncan, 2006;Dawson, 1985;Hope and Wilkinson, 1982;Myers et al, 2001Myers et al, , 2017Piper et al, 2006;Pledge, 1992;Price et al, 2009Price et al, , 2011Prideaux et al, 2010;Vickers-Rich et al, 1991;Roberts et al, 2001;Stirton et al, 1967;Taylor et al, 1994;Tedford et al, 2006;Travouillon et al, 2006Travouillon et al, , 2011Whitelaw 1989Whitelaw , 1991Woodhead et al, 2014). Age of split between taxa is based on oldest possible deposits containing those taxa and as such will change as more information becomes available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not sur- Results of the phylogenetic analysis with additional species added (relative branching order of these additional taxa are shown here as not resolved) against the geological time scale (Gradstein et al, 2012). Age span of deposits containing all known wombat taxa are provided, with black bars indicating certainty (such as radiometrically dated sites) and grey indicating uncertainty (ages are based on Archer and Wade, 1976;Archer et al, 1989Archer et al, , 1997Archer et al, , 2016Arena et al, 2016;Beck, 2008;Beheregaray et al, 2000;Black et al, 2012b;Cupper and Duncan, 2006;Dawson, 1985;Hope and Wilkinson, 1982;Myers et al, 2001Myers et al, , 2017Piper et al, 2006;Pledge, 1992;Price et al, 2009Price et al, , 2011Prideaux et al, 2010;Vickers-Rich et al, 1991;Roberts et al, 2001;Stirton et al, 1967;Taylor et al, 1994;Tedford et al, 2006;Travouillon et al, 2006Travouillon et al, , 2011Whitelaw 1989Whitelaw , 1991Woodhead et al, 2014). Age of split between taxa is based on oldest possible deposits containing those taxa and as such will change as more information becomes available.…”
Section: Discussionmentioning
confidence: 99%
“…It was interpreted to represent a lacustrine carbonate deposit by Archer et al (1989) and a cave deposit by Arena (2004), part of FZ B (Archer et al, 1989;Creaser, 1997;Travouillon et al, 2006Travouillon et al, , 2011 and IZ B3 by Arena et al (2016). It is estimated to be middle Miocene (c. 18 Ma) based on faunal correlations with radiometrically dated sites (Myers et al, 2017).…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Burramys brutyi (figure 3) is abundant in most Late Oligocene (25 Ma) to at least late Middle Miocene (approx. 13 Ma) species-diverse faunal assemblages from the Riversleigh World Heritage Area in NW Queensland [47][48][49][50][51]. It is also possible that it persisted until early Late Miocene time although the relevant local fauna at Riversleigh, the Encore Local Fauna (LF), has not yet been radiometrically dated.…”
Section: Background To the Plan To Conserve This Lineage Of Critically Endangered Possumsmentioning
confidence: 99%
“…Will MPPs be able to adapt to lowland wet forests in terms of climatic conditions? Myers et al [51] demonstrated a significant change in Riversleigh's Early to Middle Miocene communities between 18.0 and 13.5 Ma, an interval of time when atmospheric gas composition underwent radical change all around the world. Burramys brutyi remained an important component in all communities before and after this event despite major changes in overall marsupial diversity, an indication of its apparent environmental resilience to climate changes in lowland areas.…”
Section: Considering and Managing Risks: Qandasmentioning
confidence: 99%